Air velocity modeling velocity of the air around the trunk road train with installed rolling roof fairings - Nesterenko, Mykola; Skoryk, Maksum; Shapoval, Mykola; Nesterenko, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2019)
The new rolling roof fairing installed in the tractor non-bonnet cab main train layout constructing are given. After analyzingexisting exhausting elements installed on the tractor highway trailer and a large number of roof rails, it has been substantiatedthe expediency of installing a movable rope on the tractor roof, which can change the angle of the trailer airflow link with thecombination of two movements - vertical and horizontal. The combination of these movements enables to change the parametersof streamline. For this purpose, the basic hydraulic control scheme is designed, which has a number of advantages:the starting units movements smoothness, the ability to continuously adjust the speed in a wide range, low inertia, simplicityof management and automation, high operational reliability and resistance to overload. Due to the modern capabilities anddevelopment of sophisticated electronic control systems through the introduction of such a system in the control process ofhydraulic cylinders can ensure the system reliability, efficiency, ergonomics and safety equipment.
Keywords: main motorway; streamlined; roof fairings; hydraulic control scheme